A study on linguistic features of expressions denoting love for nature in English and Vietnamese songs - Ngô, Ánh Minh.; Nguyễn Văn Long, Ph.D. (Đà Nẵng : The University of Da Nang, 2015)
Introduction; Literature review and theoretical background; Research design and methodology; ...
Includes sources of songs and references.
Master thesis in social sciences and humanities. Field: The English language.Code: 60.22.02.01.
Keywords: The English language; linguistic features -- expressions denoting -- English and Vietnamese songs